PRE-OPERATIVE EDUCATION TO REDUCE ANXIETY: LITERATURE REVIEW - Hartanti, Rissa Widyasworo; Handayani, Lina (Universitas Ahmad Dahlan, 2021)
Background: Surgical procedure is one of the stressors that can end up with psychological disorders such as anxiety. Anxiety can lead to increased blood pressure and the risk of bleeding. Receiving detailed information on the surgical procedure is a patient's right. The information provided is expected to reduce patient anxiety and foster good relations between health workers and patients. Considering the importance of this step, we study the effect of pre-operative information before surgical procedures based on the published literature. This study aimed to summarize the previous research that elaborates on the relationship between education pre-operative and anxiety.Method: A literature review was used in this study. Google Scholar, PubMed, and ProQuest databases were chosen as data sources. We sough article published during 2016-2021. In total, 450 articles were screened using inclusion and exclusion criteria for analysis.Results: Eight articles reported that there was an effect of education on patient anxiety.Conclusion: Providing education is an effective approach to reduce patient anxiety.